Electricity generation from Nopal biogas effluent using a surface modified clay cup (cantarito) microbial fuel cell. Issue 4 (April 2019) - Kamaraj, Sathish-Kumar; Rivera, Alejandro Esqueda; Murugesan, Selvasankar; García-Mena, Jaime; Maya, Otoniel; Frausto-Reyes, Claudio; Tapia-Ramírez, José; Espino, Hector Silos; Caballero-Briones, Felipe
Abstract: A modified clay cup (cantarito) microbial fuel cell (C-MFCs) was designed to digest the biomass effluent from a nopal biogas (NBE). To improve the process, commercial acrylic varnish (AV) was applied to the C-MFCs. The experiment was performed as:Both-C-MFCs, painting of AV on both sides of the clay cup; In-C-MFCs, painting of AV on the internal side, and Out-C-MFCs painting of AV on the external side. The order for the maximum volumetric power densities were Both-C-MFCs (1841.99 mW/m 3 )>Out-C-MFCs (1023.74 mW/m 3 ) >In-C-MFCs (448.90 mW/m 3 ). The control experiment without applied varnish did not show a stable potential, supporting the idea that the acryloyl group in varnish could favor the performance. Finally, a 4-digits clock was powered with two, Both-C-MFCs connected in series; the microbial diversity in this format was explored and a well-defined bacterial community including members of the phyla Actinobacteria, Bacteroidetes, Firmicutes, Proteobacteria, Synergistetes and candidate division TM7 was found.